Wear-resistant soft mobile phone shell and preparation method thereof
A dynamically cross-linked TPU smartphone case with graphene oxide and silicone microspheres addresses the balance of flexibility and wear resistance, offering improved durability and user experience through enhanced self-repair and anti-slip features.
Patent Information
- Application Number
- CN202510532127.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-07-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing smartphone cases lack a balance in material properties, with hard plastics offering good durability but poor flexibility and soft TPU materials providing good flexibility but poor wear resistance, and often lack self-repair and effective anti-slip designs, leading to reduced durability and user experience.
A smartphone case composed of thermoplastic polyurethane (TPU) with dynamically cross-linked networks, dispersed graphene oxide, and a silicone microsphere coating to enhance flexibility, wear resistance, self-repair, and anti-slip properties.
The solution significantly improves the case's flexibility, wear resistance, self-repair capabilities, and anti-slip performance, resulting in enhanced durability and user experience.
Smart Images

Figure CN120310237A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic equipment protective accessories, in particular to a wear-resistant soft mobile phone shell and a preparation method thereof. Background Art
[0002] In recent years, with the widespread popularity of smartphones and other electronic devices, mobile phone cases, as important protective accessories for electronic devices, have become one of the indispensable products in consumers' daily lives. Mobile phone cases not only need to provide physical protection for the device, but also need to meet consumers' needs for appearance, feel, anti-slip properties, etc. Therefore, the development of mobile phone case materials that are both durable, beautiful, and functional has become a research focus in the field of electronic accessories.
[0003] In the prior art, mobile phone cases on the market are mainly made of hard plastic or soft TPU materials. Hard plastic has high mechanical strength and good wear resistance, and performs well in impact resistance and surface damage resistance, but it has high rigidity and poor flexibility. It is easy to transmit impact force when the mobile phone falls, increasing the risk of device damage. Soft TPU can provide good shock absorption effect due to its excellent flexibility and elasticity, but it has poor wear resistance and is prone to scratches, aging and surface deformation in long-term use. In addition, these mobile phone cases generally lack self-repairing ability and surface anti-slip design, resulting in a significant reduction in durability and user experience.
[0004] There are many problems with existing technologies. First, it is difficult to balance material properties. Hard materials and soft materials have their own limitations and cannot meet the requirements of flexibility and wear resistance at the same time. Second, mobile phone cases are prone to surface scratches and wear during use. Traditional materials lack effective self-repairing capabilities, which affects their service life. Third, the design of surface anti-slip performance is not scientific enough. The smooth surface leads to insufficient grip stability, and the granular anti-slip coating is easy to fall off due to poor adhesion. How to develop mobile phone case materials that have flexibility, wear resistance, self-repairing and anti-slip properties has become a key technical problem that needs to be solved in this field. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a wear-resistant and soft mobile phone case and a preparation method thereof. By constructing a dynamic cross-linked network, optimizing the dispersion of graphene oxide and designing an anti-slip coating, the problem that the existing mobile phone cases are difficult to balance flexibility, wear resistance, self-repair ability and anti-slip performance is solved.
[0006] To achieve the above objectives, the present invention is implemented by the following technical solutions: a wear-resistant soft mobile phone case and a preparation method thereof, comprising the following components in parts by mass: Thermoplastic polyurethane: 65-75 parts; Graphene oxide: 8-12 parts; Dynamic cross-linking agent: 10-15 parts; Antioxidant: 0.3 - 0.5 parts; Anti - slip particles: 2 - 5 parts.
[0007] Preferably, the sheet diameter of the graphene oxide is 0.5 - 5 μm, the thickness is 1 nm, and it is mixed with the dynamic cross - linker after ultrasonic dispersion treatment for 60 minutes.
[0008] Preferably, the antioxidant is UV - 326.
[0009] Preferably, the anti - slip particles are silicon microspheres with a particle size of 10 - 30 μm, which are coated on the surface of the mobile phone case to form an anti - slip coating with a thickness of 10 - 20 μm.
[0010] A preparation method of a wear - resistant and soft mobile phone case includes the following steps: Step 1, raw material pretreatment: The thermoplastic polyurethane particles are dried at 80℃ - 100℃ for 3 - 5 hours, the graphene oxide is dispersed in N,N - dimethylformamide solvent, ultrasonic treatment is carried out for 60 minutes, and a dynamic cross - linker is added and stirred for 15 - 18 minutes to obtain a mixed dispersion; Step 2, construction of dynamic cross - linked network: The dried thermoplastic polyurethane particles and the mixed dispersion are mixed in proportion, and high - temperature mixing is carried out by a twin - screw extruder. The temperature is set at 120 - 200℃, the rotation speed is 100 rpm - 130 rpm, and the mixing time is 15 minutes to obtain composite material particles; Step 3, injection molding: The composite material particles are placed in an injection molding machine, and injection molding is carried out under the conditions of a melting temperature of 200℃, a mold temperature of 60℃, and an injection pressure of 10 MPa - 20 MPa. After cooling for 2 minutes, demolding is carried out to obtain a preliminarily formed mobile phone case; Step 4, surface coating treatment: Silicon microspheres are sprayed on the surface of the preliminarily formed mobile phone case, the coating thickness is 10 - 20 μm, and drying is carried out at 120℃ - 130℃ for 30 - 35 minutes to form an anti - slip coating.
[0011] Preferably, the temperature of the twin - screw extruder for constructing the dynamic cross - linked network is set at 100℃ - 130℃ in the feeding zone, 170℃ - 190℃ in the mixing zone, and 190℃ - 210℃ in the discharging zone.
[0012] Preferably, the silicon microspheres of the surface coating are evenly coated by an electrostatic spraying device, the spraying pressure is 0.5 - 1 MPa, and the spraying time is 2 - 5 minutes.
[0013] Preferably, the composite material particles are cooled and cut into uniform particles with a particle size of 2 - 5 mm after extrusion.
[0014] The present invention provides a wear - resistant and soft mobile phone case and its preparation method. It has the following beneficial effects: 1. The present invention uses a disulfide-based dynamic crosslinking agent to construct a reversible dynamic crosslinking network, significantly improving the flexibility and self-healing performance of the mobile phone case. Compared with the mobile phone cases in the prior art that only rely on the flexibility of the material itself, the present invention achieves a repair rate of more than 90% for scratches through dynamic reorganization at the molecular level, effectively solving the problems of difficult self-healing and easy surface damage during the use of existing mobile phone cases.
[0015] 2. The present invention uses uniformly dispersed graphene oxide as a reinforcing agent. Through ultrasonic dispersion treatment, a stable interfacial connection network is formed in the matrix, improving the wear resistance of the material. Compared with the mobile phone case materials in the prior art where the performance is unstable due to the agglomeration of graphene oxide, the solution of the present invention significantly reduces the wear depth and increases the service life, overcoming the deficiencies of poor dispersibility and limited reinforcing effect of traditional reinforcing agents.
[0016] 3. The present invention designs a silicon microsphere anti-slip coating on the surface of the mobile phone case. By using the micro-particle structure, the friction coefficient is enhanced, significantly improving the holding stability of the mobile phone case. Compared with the problem of poor holding performance caused by the smooth surface of mobile phone cases in the prior art, the coating design of the present invention not only improves the user experience but also enhances the anti-wear ability of the material, solving the technical defects of easy particle shedding and short-lasting effect in traditional anti-slip designs.
[0017] 4. The present invention realizes the balance between flexibility and mechanical properties by optimizing the synergistic effect of the TPU matrix and multi-functional additives, enabling the mobile phone case to have excellent mechanical properties while maintaining a good hand feel. Compared with the mobile phone cases in the prior art where the materials cannot balance flexibility and durability due to single performance, the technical solution of the present invention effectively improves the comprehensive performance of the material, overcoming the deficiencies of poor wear resistance of flexible materials and poor hand feel of hard materials in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic flow chart of the method of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0020] Example 1: Please refer to the attached Figure 1 , the embodiment of the present invention provides a wear-resistant and flexible mobile phone case and its preparation method, including: 1. Material formula Prepare the wear-resistant and soft mobile phone case material according to the following parts by mass: Thermoplastic polyurethane (TPU): 70 parts Graphene oxide (GO): 10 parts Dynamic crosslinking agent (dibenzoyl disulfide, DTDP): 12 parts Antioxidant (UV-326): 0.4 parts Anti-slip particles (silica microspheres): 3 parts Using TPU as the substrate, it provides flexibility, elasticity and shock absorption performance, serving as the structural matrix of the entire composite material. The combination of its hard and soft segment molecular structures ensures stable basic mechanical properties.
[0021] As a two-dimensional reinforcing agent, graphene oxide is dispersed in the TPU matrix. Through the hydrogen bonding interaction between its surface hydroxyl groups and the hard segments of TPU, the wear resistance and mechanical strength are significantly improved.
[0022] Through the mechanism of disulfide bond cleavage and recombination, the dynamic crosslinking agent forms a dynamic crosslinking network under heating or shearing conditions, realizing the synergistic optimization of flexibility and wear resistance, and at the same time endowing the material with good self-healing performance.
[0023] The antioxidant protects the material from ultraviolet degradation and improves weather resistance. The silica microspheres, as anti-slip particles, are evenly coated on the surface of the material to enhance the stability of holding the mobile phone case.
[0024] 2. Preparation method 2.1 Raw material pretreatment Place the TPU particles in a vacuum drying oven and dry them at 80 °C for 4 hours to remove the adsorbed moisture and avoid the generation of bubbles inside the material during subsequent processing.
[0025] Add the graphene oxide powder to the N,N-dimethylformamide (DMF) solvent and disperse it at a concentration of 1%. Use an ultrasonic disperser (power 300 W, frequency 20 kHz) to process for 60 minutes to form a uniform dispersion.
[0026] Add the dynamic crosslinking agent DTDP to the graphene oxide dispersion and stir for 15 minutes to ensure the uniform dispersion of the crosslinking agent and form a stable reaction mixture.
[0027] The drying treatment of TPU avoids processing defects caused by hygroscopicity and ensures material uniformity.
[0028] Through ultrasonic dispersion treatment, the lamellar structure of graphene oxide is fully unfolded, the hydroxyl and carboxyl functional groups are activated, and its compatibility with the matrix material is greatly improved.
[0029] The dispersion of the dynamic crosslinking agent ensures the uniform construction of the dynamic crosslinking network under subsequent high-temperature conditions.
[0030] 2.2 Construction of Dynamic Crosslinking Network Mix the dried TPU particles with the dispersion liquid in proportion and transfer them to a twin-screw extruder.
[0031] Temperature zone settings of the extruder: Feeding zone: 120 °C; Mixing zone: 180 °C; Discharging zone: 200 °C.
[0032] Set the rotational speed of the extruder to 100 rpm and the mixing time to 15 minutes.
[0033] The extruded material is cut into uniform particles with a diameter of 2 - 5 mm after cooling.
[0034] Under the action of high temperature and shear force, the disulfide bonds break to form free radicals, which simultaneously undergo a synergistic reaction with the molecular chain segments of the TPU matrix to construct a dynamic crosslinking network. This network provides the synergistic performance of flexibility and wear resistance of the material through the dynamic reversibility of the disulfide bonds.
[0035] The graphene oxide sheets are uniformly dispersed during the mixing process, and significantly enhance the mechanical properties of the composite material through interfacial interactions.
[0036] 2.3 Injection Molding Place the composite material particles prepared after extrusion into the hopper of an injection molding machine and set the following parameters: Melting temperature: 200 °C; Mold temperature: 60 °C; Injection pressure: 10 MPa; Cooling time: 2 minutes.
[0037] After injection molding, demold to obtain the preliminary blank of the mobile phone case.
[0038] During melting and injection molding, the dynamic crosslinking network remains stable, ensuring high uniformity and mechanical properties of the material.
[0039] After the mold cools, the network of the dynamic crosslinking structure solidifies, making the shape and size of the mobile phone case precise and the performance stable.
[0040] 2.4 Surface Coating Treatment Spray silicon microsphere particles on the surface of the preliminary blank of the mobile phone case, set the spray pressure to 0.5 - 1 MPa, and control the coating thickness to be 10 - 20 μm.
[0041] Place the sprayed mobile phone case in an oven at 120 °C and cure it for 30 minutes to ensure uniform adhesion of the coating.
[0042] During spraying, the silicon microspheres are uniformly distributed on the surface of the mobile phone case through electrostatic and mechanical actions to form an anti-slip structure.
[0043] The curing treatment enhances the adhesion of the particles and the durability of the coating, while providing a surface performance with a high friction coefficient, improving the user's gripping experience.
[0044] 3. Performance Testing Abrasion Resistance Testing Test method: Use a Taber abrasion tester to conduct 5000 friction cycle tests under the conditions of a 500g load and 60 rpm.
[0045] Result: The wear depth on the material surface is less than 0.05 mm.
[0046] The lamellar structure of graphene oxide acts as a physical barrier, delaying the consumption of the wear layer; the dynamic crosslinking network disperses stress through the dynamic adjustment of molecular chains, further enhancing the abrasion resistance.
[0047] Flexibility Performance Testing Test method: Use a three-point bending tester with a support span of 30 mm and a loading speed of 1 mm / min. The test sample size is 50 mm × 10 mm × 2 mm.
[0048] Result: The bending modulus is approximately 20 MPa, and the material exhibits excellent flexibility.
[0049] The soft segments of TPU provide the basic flexibility, and the dynamic crosslinking network enhances the impact resistance through the stress dispersion mechanism.
[0050] Self-healing Performance Testing Test method: Use a scratch tester to scratch a 50-μm deep scratch on the material surface. Place the sample in an 80°C environment for 1 hour and test the repair depth.
[0051] Result: The scratch repair rate reaches over 90%.
[0052] The disulfide bonds in the dynamic crosslinking network break to form free radicals under heating conditions, and then recombine to form a new crosslinked structure, restoring the surface integrity of the material.
[0053] Anti-slip Performance Testing Test method: Measure the static friction coefficient of the coating surface.
[0054] Result: The friction coefficient increases by 20%, and the gripping stability is significantly enhanced.
[0055] The microscopic structure of the silica microsphere particles increases the contact area, significantly enhancing the surface friction force.
[0056] Example Two: 1. Material Formula Prepare a wear-resistant and soft mobile phone case using the following components in parts by mass: Thermoplastic polyurethane (TPU): 67 parts Graphene Oxide (GO): 9 parts Dynamic crosslinking agent (dibenzoyl disulfide, DTDP): 14 parts Antioxidant (UV-326): 0.3 parts Anti-slip particles (silica microspheres): 4 parts The proportion of the dynamic crosslinking agent is increased to 14 parts, increasing the density of the crosslinking network, improving the dynamic reversible performance, and further optimizing the self-healing ability of the material.
[0057] Increase the proportion of anti-slip particles to 4 parts, enhance the density of the coating particles, and further improve the anti-slip effect of the surface of the mobile phone case when held.
[0058] The proportion of graphene oxide is kept moderate, taking into account the wear resistance and cost of the material.
[0059] 2. Preparation method 2.1 Raw material pretreatment Put the TPU particles into a vacuum drying oven and dry them at 80 °C for 4 hours to ensure that there is no residual moisture in the material.
[0060] Add 9 parts of graphene oxide powder to 150 mL of N,N-dimethylformamide (DMF), and use an ultrasonic disperser to process it for 60 minutes (power 300 W, frequency 20 kHz) to uniformly disperse its lamellae and form a stable dispersion.
[0061] Add the dynamic crosslinking agent (DTDP) to the graphene oxide dispersion and stir for 20 minutes to ensure its complete dissolution and uniform distribution.
[0062] 2.2 Construction of dynamic crosslinking network After mixing the TPU particles with the above dispersion in proportion, put them into a twin-screw extruder; Extruder temperature zone settings: Feeding zone: 120 °C; Mixing zone: 190 °C; Discharging zone: 210 °C; Extruder rotation speed: 100 rpm; Extrusion time: 15 minutes.
[0063] After the extruded material is cooled, cut it into granular materials with a diameter of 3 mm by a granulator for injection molding.
[0064] 2.3 Injection molding and coating treatment Injection molding: Inject the particles at a melting temperature of 200 °C and a mold temperature of 60 °C. The injection pressure is set to 10 MPa, and the cooling time is 2 minutes to form a preliminary mobile phone case.
[0065] Surface coating treatment: Spray silicon microspheres on the surface of the preliminary mobile phone case, with a spraying pressure of 0.5 - 1 MPa, and control the coating thickness to be 15 μm; Place the sprayed mobile phone case in a drying oven at 120 °C for 30 minutes to ensure the uniformity and adhesion of the coating.
[0066] 3. Performance testing and result analysis Wear resistance testing method: Use a Taber abrasion tester to conduct 5000 friction cycle tests under the conditions of a 500 g load and 60 rpm.
[0067] Result: The wear depth on the material surface is 0.04 mm, and the wear resistance is improved by 15% compared with Example 1.
[0068] After increasing the proportion of the dynamic crosslinking agent, the crosslinking network density increases, and the synergistic effect between molecular chains is enhanced, further improving the wear resistance.
[0069] Self-healing performance testing Method: Repair the scratch at 80 °C and test the repair rate.
[0070] Result: The scratch repair rate reaches 94%.
[0071] Increasing the proportion of the crosslinking agent improves the efficiency of disulfide bond breakage and recombination, and significantly enhances the self-healing ability.
[0072] Anti-slip performance testing Method: Evaluate the holding performance by testing the static friction coefficient.
[0073] Result: The friction coefficient is increased by 25%, and the surface holding stability is significantly enhanced.
[0074] After increasing the proportion of anti-slip particles, the particle distribution density increases, and the contact area with the surface increases, thereby enhancing the friction force.
[0075] Example 3: Preparation of a wear-resistant and flexible mobile phone case with a reduced proportion of graphene oxide 1. Material formula Prepare a wear-resistant and flexible mobile phone case using the following components in parts by mass: Thermoplastic polyurethane (TPU): 72 parts Graphene oxide (GO): 7 parts Dynamic crosslinking agent (dibenzoyl disulfide, DTDP): 13 parts Antioxidant (UV-326): 0.5 part Anti-slip particles (silicon microspheres): 3 parts The proportion of TPU is increased to 72 parts to further enhance the flexibility and processability of the material; The proportion of graphene oxide is reduced to 7 parts, reducing the amount of reinforcing agent and the production cost, while maintaining a certain wear resistance; the proportion of antioxidant is increased to 0.5 part to improve the weather resistance and anti-aging performance of the material 2. Preparation method 2.1 Pretreatment of raw materials The TPU particles are placed in a vacuum drying oven at 80 °C and dried for 4 hours; The graphene oxide powder is added to N,N-dimethylformamide (DMF) at a concentration of 0.8%, and ultrasonically dispersed for 50 minutes; the dynamic crosslinking agent is added to the graphene oxide dispersion, and stirred for 10 minutes before use.
[0076] 2.2 Construction of dynamic crosslinking network The TPU particles and the dispersion are mixed in proportion and then fed into a twin-screw extruder; Extruder temperature zone settings: Feeding zone: 110 °C; Mixing zone: 170 °C; Discharging zone: 190 °C; Extruder speed: 90 rpm; Extrusion time: 15 minutes.
[0077] After cooling, the material is cut into particles with a diameter of 4 mm for injection molding.
[0078] 2.3 Injection molding and coating treatment Injection molding: The particles are injection molded at a melting temperature of 200 °C and a mold temperature of 60 °C, and demolded after cooling for 3 minutes; Coating treatment: Silica microspheres (particle size 10-30 μm) are sprayed on the surface, the coating thickness is 10 μm, and the spraying pressure is 0.5 MPa; Curing temperature 115 °C, curing time 20 minutes.
[0079] 3. Performance testing and result analysis Wear resistance testing Method: Taber abrasion tester, 5000 times friction test.
[0080] Result: The wear depth is 0.06 mm, slightly lower than that of Example 1.
[0081] Mechanism analysis: After reducing the proportion of graphene oxide, the effect of the reinforcing agent is slightly weakened, but the wear resistance is still significantly better than that of traditional TPU materials.
[0082] Flexibility performance testing Method: Three-point bending test.
[0083] Result: The bending modulus is 18 MPa, and the flexibility performance is improved compared with Example 1.
[0084] Increasing the proportion of TPU further enhances the flexibility of the matrix, while the dynamic crosslinking network maintains the mechanical stability of the material.
[0085] Self-healing performance test Method: Scratch repair at 80 °C.
[0086] Result: The repair rate is 88%.
[0087] The dynamic crosslinking network still maintains good self-healing ability, but due to the relatively low crosslinking density, the repair rate is slightly lower.
[0088] Comparative example 1: Reducing the amount of dynamic crosslinking agent 1. Material formula Prepared with the following parts by mass of raw materials: Thermoplastic polyurethane (TPU): 67 parts Graphene oxide (GO): 9 parts Dynamic crosslinking agent (dibenzoyl disulfide, DTDP): 8 parts (reducing the amount of dynamic crosslinking agent) Antioxidant (UV-326): 0.3 parts Anti-slip particles (silica microspheres): 4 parts 2. Preparation method Raw material pretreatment: The drying conditions of TPU particles are the same as those in Example 2; The dispersion conditions of graphene oxide are the same as those in Example 2; The dynamic crosslinking agent is added to the dispersion liquid and stirred for 20 minutes.
[0089] Dynamic crosslinking network construction: The temperature zones of the twin-screw extruder are set the same as those in Example 2: the feeding zone is 120 °C, the mixing zone is 190 °C, the discharging zone is 210 °C, and the rotation speed is 100 rpm; The extrusion time is 15 minutes, and after cooling, it is cut into particles with a diameter of 3 mm.
[0090] Injection molding and coating treatment: The injection molding conditions are the same as those in Example 2; Silica microspheres are spray-coated on the surface, the spray thickness is 15 μm, the curing temperature is 120 °C, and the curing time is 30 minutes.
[0091] Comparative example 2: Not using a dynamic crosslinking agent 1. Material formula Prepared with the following parts by mass of raw materials: Thermoplastic polyurethane (TPU): 67 parts Graphene oxide (GO): 9 parts No dynamic crosslinking agent is added Antioxidant (UV-326): 0.3 parts Anti-slip particles (silica microspheres): 4 parts 2. Preparation method Raw material pretreatment: The drying conditions of TPU particles are the same as those in Example 2; The dispersion conditions of graphene oxide are the same as those in Example 2.
[0092] Dynamic crosslinking network construction: After mixing the dried TPU particles and the dispersion liquid in proportion, put them into a twin-screw extruder; Temperature zone settings of the extruder: feeding zone 120°C, mixing zone 190°C, discharging zone 210°C; Extrusion time is 15 minutes, and after cooling, cut into particles with a diameter of 3 mm.
[0093] Injection molding and coating treatment: The injection molding conditions are the same as those in Example 2; Spray silica microspheres on the surface, spray thickness 15 μm, curing temperature 120°C, curing time 30 minutes.
[0094] Comparative Example 3: Graphene oxide is not fully dispersed 1. Material formula Prepared with the following parts by mass of raw materials: Thermoplastic polyurethane (TPU): 72 parts Graphene oxide (GO): 7 parts Dynamic crosslinking agent (dibenzoyl disulfide, DTDP): 13 parts Antioxidant (UV-326): 0.5 parts Anti-slip particles (silica microspheres): 3 parts 2. Preparation method Raw material pretreatment: The drying conditions of TPU particles are the same as those in Example 3; Graphene oxide powder is added to N,N-dimethylformamide (DMF) and stirred and mixed, but no ultrasonic dispersion treatment is carried out, and only magnetic stirring is carried out for 30 minutes to form a dispersion liquid; The dynamic crosslinking agent is added to the dispersion liquid and stirred for 10 minutes.
[0095] Dynamic crosslinking network construction: The temperature zone settings of the twin-screw extruder are the same as those in Example 3: feeding zone 110°C, mixing zone 170°C, discharging zone 190°C, rotation speed 90 rpm; Extrusion time is 15 minutes, and after cooling, cut into particles with a diameter of 4 mm.
[0096] Injection molding and coating treatment: The injection molding conditions are the same as those in Example 3; The surface is spray-coated with silicon microspheres, the coating thickness is 10 μm, the curing temperature is 115 °C, and the curing time is 20 minutes.
[0097] Comparative Example 4: No anti-slip particle coating is added 1. Material formulation It is prepared with the following parts by mass of raw materials: Thermoplastic polyurethane (TPU): 72 parts Graphene oxide (GO): 7 parts Dynamic crosslinking agent (dibenzoyl disulfide, DTDP): 13 parts Antioxidant (UV-326): 0.5 part 2. Preparation method Raw material pretreatment: The drying of TPU, the dispersion of graphene oxide, and the treatment of the dynamic crosslinking agent are all the same as those in Example 3.
[0098] Dynamic crosslinking network construction: The temperature zones of the twin-screw extruder are set as follows: the feeding zone is 110 °C, the mixing zone is 170 °C, the discharging zone is 190 °C, and the rotation speed is 90 rpm; After cooling, the material is cut into particles with a diameter of 4 mm.
[0099] Injection molding: The injection molding conditions are the same as those in Example 3, but the surface coating spraying and curing treatments are not carried out.
[0100] Comparative Example 5: Increase the amount of graphene oxide 1. Material formulation It is prepared with the following parts by mass of raw materials: Thermoplastic polyurethane (TPU): 70 parts Graphene oxide (GO): 15 parts (increase the amount of graphene oxide) Dynamic crosslinking agent (dibenzoyl disulfide, DTDP): 12 parts Antioxidant (UV-326): 0.4 part Anti-slip particles (silicon microspheres): 3 parts 2. Preparation method Raw material pretreatment: The drying conditions of TPU are the same as those in Example 1; The dispersion conditions of graphene oxide are the same as those in Example 1.
[0101] Dynamic crosslinking network construction: The temperature zones of the twin-screw extruder are set as follows: the feeding zone is 120 °C, the mixing zone is 180 °C, the discharging zone is 200 °C, and the rotation speed is 100 rpm; After cooling, the material is cut into particles with a diameter of 3 mm.
[0102] Injection molding and coating treatment: The injection molding conditions are the same as those in Example 1; Silica microspheres are spray-coated on the surface, with a spray thickness of 10 μm, a curing temperature of 120 °C, and a curing time of 30 minutes.
[0103] Experiment 1: Influence of dynamic crosslinking agent on the self-healing performance of materials Purpose of experimental design: By comparing the dosages of the dynamic crosslinking agent (Example 2: 14 parts, Comparative Example 1: 8 parts, Comparative Example 2: no dynamic crosslinking agent added), evaluate its influence on the self-healing performance of the materials, and verify the dynamic fracture and recombination ability of the dynamic crosslinked network in a high-temperature environment.
[0104] Experimental equipment and materials Scratch tester: AntonPaar RST3 Thermostatic oven: Binder FD115 Surface profiler: Bruker Dektak XT Samples: Mobile phone case samples prepared from the materials of Example 2, Comparative Example 1, and Comparative Example 2 Experimental procedure Sample preparation: Take samples of the same size (50 mm × 50 mm × 2 mm) from the materials of Example 2, Comparative Example 1, and Comparative Example 2.
[0105] Use the scratch tester to scratch each sample surface with a scratch width of 50 μm and a depth of 20 μm, and control the scratch length to 10 mm to ensure consistent scratch morphology.
[0106] Check the initial scratch depth and record the initial data with the surface profiler.
[0107] Put the scratched samples into the thermostatic oven and keep them at 80 °C for 1 hour.
[0108] During the constant temperature process, the disulfide bonds in the dynamic crosslinked network on the sample surface break and recombine, resulting in self-healing behavior.
[0109] Take out the samples after repair, cool them to room temperature, and measure the depth change of the scratches again with the surface profiler.
[0110] Calculate the repair efficiency: Experimental settings Thermostatic oven temperature: 80 °C; Insulation time: 1 hour; Each group of samples is tested 3 times, and the average value is taken to ensure data accuracy and repeatability.
[0111] Table 1: Experimental data on the influence of dynamic crosslinking agent on the self-healing performance of materials The samples in Example 2 exhibited excellent self-healing performance with a healing efficiency close to 90%, which was much higher than that of Comparative Example 1 and Comparative Example 2. The reason is that the high proportion of dynamic cross-linking agent stimulated more disulfide bond breakage and recombination in an 80 °C environment. This network recombination behavior not only filled the scratched area but also formed a stronger cross-linked structure during the healing process. Therefore, a high proportion of the dynamic cross-linking agent can significantly improve the self-healing performance.
[0112] In Comparative Example 1, although there was still a dynamic cross-linking agent, due to the insufficient dosage, the density of the cross-linked network was low, resulting in limited efficiency of breakage and recombination. The material showed low scratch filling ability during the healing process, and the average healing efficiency was only about 70%. This indicates that the dosage of the dynamic cross-linking agent directly determines the activity of the cross-linked network and the healing efficacy.
[0113] In Comparative Example 2, no dynamic cross-linking agent was added at all, and the self-healing behavior was hardly visible. The recovery of the scratch depth could only rely on the high-temperature softening of the material, and this physical recovery was not only inefficient but also likely to cause a decrease in the surface mechanical properties. This result shows that the introduction of the dynamic cross-linking agent is the key to achieving molecular-level dynamic repair. Materials without a cross-linked network cannot obtain the ability of dynamic recombination even if they have flexibility.
[0114] Experiment 2: Effect of the amount of graphene oxide on the wear resistance of the material Experimental description Experimental purpose: To explore the effect of the amount of graphene oxide on the wear resistance of the material, and evaluate the effect of the content and dispersion state of graphene oxide on the surface wear resistance of the material by comparing the wear resistance of Example 1 (the amount of graphene oxide is 10 parts), Comparative Example 5 (the amount is increased to 15 parts), and Comparative Example 3 (graphene oxide is not fully dispersed).
[0115] Experimental equipment and materials Taber abrasion tester: Taber5135 Abrasive wheel model: CS-10 Samples: Mobile phone case samples prepared in Example 1, Comparative Example 5, and Comparative Example 3 Experimental steps Sample preparation Take samples with dimensions of 50 mm × 50 mm × 2 mm from Example 1, Comparative Example 5, and Comparative Example 3 respectively to ensure consistent dimensions.
[0116] Test preparation Install a CS-10 abrasive wheel on the Taber abrasion tester, apply a load of 500 g, and adjust the rotation speed to 60 rpm.
[0117] Clean the surface of each group of samples to ensure that there are no particles or contaminants interfering with the test.
[0118] Abrasion resistance test Fix the sample on the sample stage of the Taber abrasion tester, turn on the equipment, and set the friction cycle number to 5000 times.
[0119] After the test, measure the wear depth of the sample surface in millimeters (mm).
[0120] Data recording and repeated testing Repeat the test 3 times for each group of samples, record the wear depth and take the average value.
[0121] Experimental setup Wheel material: Alumina Rotation speed: 60 rpm Perform 3 tests on each group of samples and take the average value.
[0122] Table 2: Experimental data on the effect of graphene oxide dosage on the abrasion resistance of materials In Example 1, the dosage of graphene oxide is 10 parts, and the average wear depth of the test sample is 0.032 mm, showing good abrasion resistance. This performance is mainly due to the two-dimensional sheet structure of graphene oxide, which forms a uniform reinforcement network in the matrix. The well-dispersed graphene oxide sheets play a physical barrier role, reducing the shedding of surface substances during the wear process, and further enhancing the abrasion resistance of the material through the hydrogen bond interaction between it and the TPU matrix.
[0123] For Comparative Example 5, the dosage of graphene oxide is increased to 15 parts, but the abrasion resistance does not increase but decreases, and the average wear depth reaches 0.050 mm. This is because after excessive addition of graphene oxide, the stacking phenomenon between the sheets intensifies, and the dispersion uniformity drops significantly, resulting in a discontinuous reinforcement network in the matrix. During the friction process, the stacked graphene oxide sheets are easily detached from the matrix, accelerating the wear of the material surface instead. It can be seen that the dosage of graphene oxide needs to be optimized within a certain range, and excessive addition is not only ineffective but even harmful.
[0124] The test results of Comparative Example 3 show that the sample of graphene oxide with insufficient dispersion exhibits the worst abrasion resistance, with an average wear depth of 0.077 mm. The graphene oxide without ultrasonic treatment forms large particle aggregates in the matrix, and these aggregates are easily detached during friction, causing serious wear of the material surface. At the same time, the interfacial reinforcement effect of graphene oxide is almost lost, and the material can only rely on the flexibility of TPU itself to resist wear, while the abrasion resistance of the TPU matrix alone is relatively weak and cannot meet the high-performance requirements.
[0125] Experiment 3: Influence of Coating Design on Anti-slip Performance Experiment Description The purpose of the experiment is to verify the role of the silicon microsphere coating in improving the anti-slip performance of the mobile phone case surface. By comparing the samples of Example 3 (with silicon microsphere coating) and Comparative Example 4 (without silicon microsphere coating), the influence of the anti-slip coating on the holding performance of the material is analyzed.
[0126] Experiment Equipment and Materials Coefficient of Friction Tester: Rtec MFT5000 Samples: Mobile phone case samples prepared in Example 3 and Comparative Example 4 Experiment Steps Sample Preparation Take samples of the same size (50mm×50mm×2mm) from the materials of Example 3 and Comparative Example 4 respectively to ensure consistent comparison conditions.
[0127] Test Preparation Fix the sample on the sample stage of the friction tester.
[0128] Adjust the tester parameters, apply a load of 10N, and set the sliding speed to 5mm / s.
[0129] Anti-slip Performance Test Start the tester and measure the static coefficient of friction between the sample surface and the silicone test plate.
[0130] Repeat the test 5 times, record the coefficient of friction and take the average value.
[0131] Experiment Settings Environmental Conditions: Room temperature 25°C, humidity 50%.
[0132] Loading Force: 10N.
[0133] Sliding Speed: 5mm / s.
[0134] Table 3: Experimental Data of the Influence of Coating Design on the Anti-slip Performance of Materials The presence of the coating makes the sample of Example 3 show significantly better anti-slip performance than that of Comparative Example 4, and its average static coefficient of friction is close to 0.785. This is mainly due to the microscopic rough structure formed by the silicon microsphere coating. When the silicon microspheres are more evenly distributed, the surface coefficient of friction is significantly improved, and a stronger mechanical locking effect is formed between the particles. This effect effectively prevents the relative movement of the sliding interface and significantly improves the holding stability.
[0135] Comparative Example 4 has no coating at all, and its average static friction coefficient is only 0.342. Due to the lack of micro-particle support, the smooth TPU matrix has extremely low friction when contacting the silicone surface. Under the action of the sliding load, slippage is likely to occur at the interface. The mobile phone case lacking surface modification design not only has poor anti-slip effect, but also has a significantly inferior user experience.
[0136] In addition, the anti-slip performance of the silicon microsphere coating also comes from the synergistic effect of its particle size and distribution. In Example 3, after optimizing the particle size (10 - 30 μm) of the silicon microspheres and the coating thickness (10 - 20 μm), the mechanical stability of the coating is ensured. In Comparative Example 4, the complete absence of the coating makes the surface properties of the material unable to be optimized, and relying solely on the friction performance of the substrate cannot meet the requirements of high anti-slip performance.
[0137] Experiment 4: Influence of the dosage of dynamic crosslinking agent on the flexibility of the material Experiment description Experiment purpose: By comparing Example 2 (dosage of dynamic crosslinking agent is 14 parts) and Comparative Example 1 (dosage of dynamic crosslinking agent is 8 parts), evaluate the influence of the dosage of dynamic crosslinking agent on the flexible performance of the material, and analyze the effect of the crosslinking network density on the bending performance of the material.
[0138] Experimental equipment and materials Three-point bending tester: Instron5944 material testing machine Samples: Mobile phone case samples prepared in Example 2 and Comparative Example 1 Experimental procedure Sample preparation Take samples of the same size (50 mm × 10 mm × 2 mm) from the materials of Example 2 and Comparative Example 1 respectively, ensuring that there are no obvious defects in the sample thickness and surface.
[0139] Test preparation Install the sample on the three-point bending test fixture and set the support span to 30 mm.
[0140] Adjust the loading speed to 1 mm / min, and apply a small preload at the beginning of the test to ensure that the sample is fixed.
[0141] Flexible performance test Start the tester and record the load and displacement data of the sample during the bending process.
[0142] Calculate the bending modulus according to the stress-strain curve to measure the flexible performance of the sample.
[0143] Data recording Each group of samples is tested 5 times repeatedly, record the bending modulus data, and take the average value.
[0144] Experimental settings Support span: 30 mm Sample size: 50 mm × 10 mm × 2 mm Loading rate: 1 mm / min Each group of samples was tested 5 times.
[0145] Table 4: Experimental data on the effect of the amount of dynamic crosslinking agent on the flexibility of the material The effect of the content of the dynamic crosslinking agent on the flexibility of the material was particularly significant in the test. The average flexural modulus of the samples in Example 2 was 20.4 MPa, showing relatively high flexibility, which benefited from the high proportion of the dynamic crosslinking agent to construct a dense crosslinking network. Under the action of bending stress, this network structure can effectively disperse the stress, reduce local stress concentration, and at the same time allow the molecular chain segments to perform reversible sliding within a certain range, and the material shows relatively high bending resistance.
[0146] In Comparative Example 1, due to the reduction in the amount of the dynamic crosslinking agent, the density of the crosslinking network decreased significantly, resulting in the flexural modulus of the sample dropping to 16.3 MPa. The insufficient number of crosslinking points limited the dynamic adjustment ability of the molecular chain segments, and the material was prone to plastic deformation under external forces. In addition, due to the lack of sufficient crosslinking support, the relaxation time of the molecular chain segments became shorter, further reducing the flexibility.
[0147] The density of the crosslinking network not only affects the mechanical properties of the material but also its dynamic behavior. In Example 2, the dynamic crosslinking network can quickly respond to stress changes during the bending process and shows excellent elastic recovery ability. While in Comparative Example 1, due to the reduction in the number of dynamic crosslinking points, the dynamic responsiveness of the network decreased significantly, resulting in poor bending performance of the material.
[0148] Experiment 5: Effect of the dispersion uniformity of graphene oxide on the mechanical properties and wear resistance of the material Experimental description Experimental purpose: By comparing Example 3 (ultrasonic dispersion of graphene oxide) and Comparative Example 3 (inadequate dispersion of graphene oxide), analyze the effect of dispersion uniformity on the mechanical properties and wear resistance of the material. Study the interfacial action and enhancement effect differences formed by the dispersion method of graphene oxide in the composite material.
[0149] Experimental equipment and materials Taber abrasion tester: Taber5135 Tensile testing machine: Instron5944 Scanning electron microscope (SEM): HitachiSU5000 Samples: Mobile phone case samples prepared in Example 3 and Comparative Example 3 Experimental procedures Sample preparation Take samples with dimensions of 50 mm × 50 mm × 2 mm from the materials of Example 3 and Comparative Example 3, ensuring that the surface is uniform and free of cracks.
[0150] Abrasion resistance test Use a Taber abrasion tester to measure the wear depth of the samples.
[0151] The grinding wheel model is CS-10, the load is set to 500 g, the rotation speed is 60 rpm, and the number of test cycles is 5000 times.
[0152] Record the wear depth of the sample surface after the test (unit: mm).
[0153] Mechanical property test Use a tensile testing machine to test the tensile properties of the samples.
[0154] The sample size is 100 mm × 10 mm × 2 mm, and the tensile speed is 50 mm / min.
[0155] Record the tensile strength data (unit: MPa).
[0156] Characterization of dispersion uniformity Use SEM to observe the distribution of graphene oxide in the samples.
[0157] After sputtering the sample surface with gold, place it on the SEM sample stage, and observe and record the dispersion state of the graphene oxide sheets.
[0158] Experimental setup Abrasion test load: 500 g Tensile speed: 50 mm / min SEM acceleration voltage: 10 kV.
[0159] Table 4: Experimental data on the effect of graphene oxide dispersion uniformity on material properties Example 3 demonstrated significantly better abrasion resistance and tensile properties than Comparative Example 3. The average wear depth was 0.038 mm, significantly lower than 0.082 mm of Comparative Example 3, which was attributed to the formation of an effective reinforcement network by uniformly dispersed graphene oxide in the matrix. Well-dispersed graphene oxide sheets acted as physical barriers during the friction process, effectively delaying the wear of the matrix. A strong interfacial interaction was formed between it and the TPU matrix, further enhancing the anti-friction performance, while these advantages were completely lost in Comparative Example 3.
[0160] In the tensile property test, the average tensile strength of the sample of Example 3 reached 32.4 MPa, significantly superior to 24.7 MPa of Comparative Example 3. This is because the ultrasonically dispersed graphene oxide is uniformly distributed in the matrix, providing a wider interfacial connection area, enabling the load to be effectively transferred to the reinforcing agent. In contrast, the graphene oxide in Comparative Example 3 formed large particle aggregates due to non-uniform dispersion. Not only could it not play a reinforcing role, but it also became stress concentration points, resulting in a decline in the overall mechanical properties of the material.
[0161] In addition, SEM characterization shows that the graphene oxide sheets in the sample of Example 3 are uniformly distributed and there is no obvious agglomeration phenomenon, while there are more large particle aggregates in Comparative Example 3, and the reinforcing effect is lost in local areas. This further confirms the decisive role of the dispersion method of graphene oxide on the properties of the composite material. The uniformly dispersed reinforcing agent can form a complete and effective physical and chemical reinforcing network, while the non-uniformly dispersed reinforcing agent is prone to weakening the matrix properties.
[0162] Experiment 6: Influence of the ratio of TPU to anti-slip particles on the feel and durability of the material Experimental description Experimental purpose: To explore the comprehensive influence of the proportion of TPU substrate and anti-slip particle coating on the surface feel and coating durability of the mobile phone case. By comparing Example 1 (70 parts of TPU used, 3 parts of anti-slip particles used) and Comparative Example 4 (without anti-slip particle coating), evaluate the role of the anti-slip particle coating in improving the surface friction performance and durability.
[0163] Experimental equipment and materials Feel test tool: A 10-person test group Abrasion machine: Taber5135 Samples: Mobile phone case samples prepared in Example 1 and Comparative Example 4 Experimental procedures Sample preparation Prepare samples of Example 1 and Comparative Example 4 with dimensions of 50 mm × 50 mm × 2 mm, ensuring that the surface coating is intact.
[0164] Feel test Organize 10 testers of different ages and genders to touch the surface of the sample with their fingers at room temperature.
[0165] The testers subjectively score according to the surface slip feeling, comfort and holding stability, and the scoring range is from 1 (poor) to 10 (excellent).
[0166] Collect the scoring data and calculate the average score.
[0167] Durability test Use the Taber5135 abrasion machine to conduct a durability test on the sample coating.
[0168] Apply a load of 500 g and conduct 1000 friction cycles using a CS-10 grinding wheel.
[0169] Observe the wear of the surface coating of the sample and record the coating integrity score (1 - 10, where a higher score indicates less wear).
[0170] Experimental setup Handfeel test environment: room temperature 25°C, humidity 50%.
[0171] Durability test load: 500 g Each group of samples is tested 3 times and the average value is taken.
[0172] Table 6: Experimental data on the influence of the ratio of TPU to anti-slip particles on the handfeel and durability of the material The samples of Example 1 performed excellently in the handfeel and durability tests, with an average subjective score of 8.77 and a coating integrity score of 9.00. The addition of the silica microsphere coating effectively improved the friction characteristics of the mobile phone case surface and formed a stable micro-rough structure. These microstructures can enhance the contact area between the skin and the mobile phone case surface, thereby improving the holding stability. The flexible characteristics of the TPU substrate and the silica microsphere particles work together to provide a more comfortable anti-slip experience while maintaining a soft touch.
[0173] Comparative Example 4 has no coating at all, with a smooth surface and lack of friction. Its handfeel score is only 5.37. Although the smooth TPU surface is soft, it shows obvious deficiencies in touch and holding stability, especially under wet conditions, where slippage is likely to occur. In the durability test, the absence of the coating led to obvious scratches and wear marks on the material after the friction cycles. The scoring data shows that the surface durability is poor, which is likely to affect long-term use.
[0174] The presence of the coating not only improves the anti-slip effect of the surface but also significantly enhances the wear resistance of the material. The silica microsphere particles form a wear-resistant barrier during the wear process, effectively protecting the matrix from direct external damage. Example 1 balances the relationship between handfeel, durability, and friction performance by optimizing the coating particle ratio.
[0175] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A wear-resistant and soft mobile phone case, characterized in that, Comprising the following components in parts by mass: Thermoplastic polyurethane: 65 - 75 parts; Graphene oxide: 8 - 12 parts; Dynamic crosslinking agent: 10 - 15 parts; Antioxidant: 0.3 - 0.5 parts; Anti-slip particles: 2 - 5 parts.
2. The wear-resistant and soft mobile phone case according to claim 1, wherein The graphene oxide has a sheet diameter of 0.5 - 5 μm and a thickness of 1 nm, and the dynamic crosslinking agent is benzophenone disulfide.
3. A wear-resistant and soft mobile phone case according to claim 1, characterized in that, The antioxidant is UV - 326.
4. A wear-resistant and soft mobile phone case according to claim 1, wherein, The anti-slip particles are silicon microspheres with a particle size of 10 - 30 μm, which are coated on the surface of the mobile phone case to form an anti-slip coating with a thickness of 10 - 20 μm.
5. A preparation method of a wear-resistant and soft mobile phone case, according to any one of claims 1-4, a wear-resistant and soft mobile phone case, characterized in that, Including the following steps: Step 1, raw material pretreatment: drying the thermoplastic polyurethane particles at 80°C - 100°C for 3 - 5 hours, dispersing the graphene oxide in N,N-dimethylformamide solvent, ultrasonic treatment for 60 minutes, adding the dynamic crosslinking agent and stirring for 15 - 18 minutes to obtain a mixed dispersion; Step 2, construction of dynamic crosslinking network: mixing the dried thermoplastic polyurethane particles with the mixed dispersion in proportion, performing high-temperature mixing through a twin-screw extruder, setting the temperature at 120°C - 200°C, the rotation speed at 100 rpm - 130 rpm, and the mixing time at 15 minutes to obtain composite material particles; Step 3, injection molding: placing the composite material particles in an injection molding machine, injection molding under the conditions of a melting temperature of 200°C, a mold temperature of 60°C, and an injection pressure of 10 MPa - 20 MPa, demolding after cooling for 2 minutes to obtain a preliminarily formed mobile phone case; Step 4, surface coating treatment: spraying silicon microspheres on the surface of the preliminarily formed mobile phone case, with a coating thickness of 10 - 20 μm, and drying at 120°C - 130°C for 30 - 35 minutes to form an anti-slip coating.
6. The preparation method of a wear-resistant and soft mobile phone case according to claim 5, characterized in that, The temperature of the twin-screw extruder for constructing the dynamic crosslinking network is set at 100°C - 130°C in the feeding zone, 170°C - 190°C in the mixing zone, and 190°C - 210°C in the discharging zone.
7. A method for preparing a wear-resistant and soft mobile phone case according to claim 5, characterized in that, The silicon microspheres of the surface coating are evenly coated by an electrostatic spraying device, with a spraying pressure of 0.5 - 1 MPa and a spraying time of 2 - 5 minutes.
8. A method for preparing a wear-resistant and soft mobile phone case according to claim 5, characterized in that, The composite material particles are cooled and cut into uniform particles with a particle size of 2 - 5 mm after extrusion.
Citation Information
Patent Citations
Wear-resistant and aging-resistant modified polyurethane elastomer composite material as well as preparation method and application thereof
CN116606542A
Organic silicon leather and preparation method thereof
CN118147927A
Cited By
Wear-resistant mobile phone shell sleeve and preparation method thereof
CN121652438A